The Influence of Work Dynamics, Organizational Culture on Employee Performance Through KPI - Hafzah, Tuti; Samosir, P S (Krisnadwipayana International Journal of Management Studies, 2024)
The Key Performance Indicators is an indicator for measuring employee performance. The effectiveness of the Key Performance Indicators as a execution measuring tool is certainly determined by many factors including changes in work dynamics and organizational culture. Based on this, the aim of this inquire about is to discover out and get empirical evidence of the impact of work dynamics and organizational culture on employee work performance through key performance indicators. The research was carried out in the work area of ​​the Digital Development Division of PT. Bank Negara Indonesia Tbk with a research population of 139 employee respondents in the 2022-2023 period and using the path analysis method. From the research results, the results show that Key Performance Indicators cannot always moderate work dynamics and organizational culture on worker execution. KPIs need to adjust to changes in work dynamics and organizational culture. So that the KPI achievements developed can reflect employee performance.